The Impact of Patient Prejudice on Minoritized Female Physicians - Dellasega, Cheryl; Aruma, Jane-Frances; Sood, Natasha; Andreae, Doerthe A. (Frontiers in Public Health, 2022)
Abstract Background: Patient bias and prejudice directed against physicians from diverse backgrounds is a frequent occurrence in healthcare. Female physicians have long experienced discrimination in the healthcare system based on their gender alone. The dynamic known as Patient Prejudice toward Providers (PPtP) is disproportionately affecting female physicians because it is frequently compounded by sexism. Aim: The goal of this study was to explore the impact of PPtP on female resident and attending physicians. Methods: Using transcribed one-on-one interviews from a larger study of PPtP affecting resident and attending physicians, ten interviews with female physicians (resident and attending) from diverse ethnic backgrounds and countries of training at a large academic medical center were analyzed. The authors independently reviewed the interviews using an iterative process within and across interviews to inductively identify repeating words, phrases, and concepts relevant to the study aim. Results: Demographics of the ten participants included age (mean 34.6 years), ethnicity (6 Asian, 2 Hispanic, 2 African), and country of training (10 % IMG vs. 90% US trained). Four of the interviewees were residents and six were attendings. Themes that emerged from the analysis included experiencing “A Gendered Continuum of Abuse”, “Establishing a Higher Standard of Competency”, “Overcoming the Stereotype of the White Male Physician”, “The Physicality of Self Identity”, and “The Need to be Protective of Minoritized Trainees”. All participants agreed that these perceptions created an adverse environment at the workplace and impacted on patient care. Conclusions: Discrimination of physicians based on their gender or their race/ ethnicity has been reported. This study highlights the compounded effects of patient prejudice on female minoritized physicians. Organizations and individuals should identify and implement strategies to address the impact of PPtP and sexism in order to create an environment where all women can thrive professionally.